Effects of professional development program on primary science teachers’ ICT use in China: mediation effects of science teachers’ knowledge, beliefs and instructional practice - Beibei Lv; Danhua Zhou; Zhenshan Rong; Xuewai Tian; Jingying Wang (Disciplinary and Interdisciplinary Science Education Research, 2024)
Abstract Faced with international science and technology competition, strengthening information, communication, and technology (ICT) use has become the core goal of science education. Many studies have revealed that teachers’ professional development programs could influence ICT use. However, whether the relationship could be mediated by teachers’ knowledge, beliefs, and instructional practice remains unclear, especially in the context of China. Based on the Sociocultural Model of Embedded Belief Systems, a hypothesized model from teachers’ professional development to ICT use that meditated by science teachers’ knowledge, beliefs, and instructional practices was constructed. With the Structural Equation Model (SEM) method, 131,134 Chinese primary science teachers were surveyed to detect the interrelationships among the factors in the model. The path analysis revealed that: (1) Science teachers’ professional development has not positively influenced ICT use, while science teachers’ knowledge, beliefs, and instructional practices could significantly influence science teachers’ ICT use; (2) Science teachers’ knowledge, beliefs, and instructional practices not only respectively play a mediating role but also play a chain mediating role in the process of teachers’ professional development influencing ICT use.